2018
DOI: 10.1155/2018/9823141
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Glucoraphanin‐Rich Broccoli Sprouts Inhibits Formation of Advanced Glycation End Products and Attenuates Inflammatory Reactions in Endothelial Cells

Abstract: We have previously shown that sulforaphane not only inhibits formation of advanced glycation end products (AGEs) but also exerts anti-inflammatory effects on AGE-exposed human umbilical vein endothelial cells (HUVECs) and AGE-injected rat aortae. Here we examined the effects of aqueous extract of glucoraphanin-rich broccoli sprouts on formation of AGEs and then investigated whether the extract could attenuate inflammatory or oxidative stress reactions in tumor necrosis factor-alpha (TNF-α)- or AGE-exposed HUVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Inhibition of iNOS or NO production, therefore, could mitigate oxidative stress and further inflammatory cascades in neurodegenerative diseases. Previous studies reported that broccoli sprout inhibited inflammation in endothelial cells [39] and in LPS-treated mice [13]. Additionally, sulforaphane inhibited iNOS-mediated NO production in activated microglia [40].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of iNOS or NO production, therefore, could mitigate oxidative stress and further inflammatory cascades in neurodegenerative diseases. Previous studies reported that broccoli sprout inhibited inflammation in endothelial cells [39] and in LPS-treated mice [13]. Additionally, sulforaphane inhibited iNOS-mediated NO production in activated microglia [40].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory mechanisms of broccoli sprouts are probably associated with the nuclear factor-kappa B (NF-κB) and nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathways [27]. Both in vitro and in vivo experiments, as well as clinical trials, mainly exhibit anti-inflammatory effects of broccoli sprouts, which showed high concentrations of sulforaphane and a group of phenolic compounds, including anthocyanins, isoquercetin, chlorogenic and cinnamic acids, via inhibiting inflammatory mediators such as a nitric oxide (NO), decreasing the levels of proinflammatory cytokines such as tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), and IL-1β, and increasing the levels of anti-inflammatory cytokines such as IL-10 and IL-22 [27,28,55,72,113,114]. For example, a study showed that sulforaphane-enriched broccoli sprouts inhibited activation of the NF-κB signaling pathway and the secretions of inflammatory proteins (inducible nitric oxide synthase (iNOS), cyclooxygenase 2 (COX-2), TNF-α, IL-6, IL-1β, and prostaglandin E2 (PGE2)) in microglial cells (BV2) and male ICR (Institute of Cancer Research) mice.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…It is known to have antioxidant, anti-inflammatory, anti-apoptotic, cytoprotective, and anti-diabetic effects [ 17 , 18 ]. The aqueous extract of glucoraphanin-rich broccoli sprouts inhibits AGE formation and AGE-induced inflammatory reactions in endothelial cells and rat aorta [ 19 , 20 ]. Furthermore, SFN-mediated inhibition of AGE–RAGE interaction is known to be responsible for pericyte protection against AGE-induced toxicity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%